(untitled) (Journal of Universal Science Research, 2024)
This article provides an in-depth analysis of the physicochemical properties of colloidal substances. Colloids are systems consisting of two phases, the dispersed phase and the dispersion medium, between which specific interactions occur. The optical, kinetic, and electrical properties of colloids, including the Tyndall effect, Brownian motion, electrophoresis, and electrokinetic phenomena, were analyzed. According to the research results, the particle size of the dispersed phase and its interaction with the dispersion medium determine the stabilization of colloidal systems. This article not only expands existing knowledge about colloidal substances but also creates a basis for further studying their applications in pharmaceuticals, the food industry, and other fields.